Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1038/35081080
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with the NMDA receptor locks CaMKII in an active conformation

Abstract: Calcium- and calmodulin-dependent protein kinase II (CaMKII) and glutamate receptors are integrally involved in forms of synaptic plasticity that may underlie learning and memory. In the simplest model for long-term potentiation, CaMKII is activated by Ca2+ influx through NMDA (N-methyl-D-aspartate) receptors and then potentiates synaptic efficacy by inducing synaptic insertion and increased single-channel conductance of AMPA (alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid) receptors. Here we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
843
4
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 635 publications
(882 citation statements)
references
References 29 publications
31
843
4
4
Order By: Relevance
“…Localization of CaMKII at the PSD has been proposed to be critical for its role in LTP (Lisman et al, 2002;Barria and Malinow, 2005). Furthermore, several different forms of neuronal activation, including treatments that lead to synaptic potentiation, have been shown to induce translocation of CaMKII to post-synaptic sites (Strack et al, 1997b;Shen and Meyer, 1999;Otmakhov et al, 2004;Dosemeci et al, 2001;Bayer et al, 2001). Accordingly, a more complete knowledge of the molecular mechanisms that regulate CaMKII binding to the PSD is likely to be crucial for our understanding of the biochemical events that occur during LTP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Localization of CaMKII at the PSD has been proposed to be critical for its role in LTP (Lisman et al, 2002;Barria and Malinow, 2005). Furthermore, several different forms of neuronal activation, including treatments that lead to synaptic potentiation, have been shown to induce translocation of CaMKII to post-synaptic sites (Strack et al, 1997b;Shen and Meyer, 1999;Otmakhov et al, 2004;Dosemeci et al, 2001;Bayer et al, 2001). Accordingly, a more complete knowledge of the molecular mechanisms that regulate CaMKII binding to the PSD is likely to be crucial for our understanding of the biochemical events that occur during LTP.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from promoting Ca 2+ -independent activity of CaMKII, T286 phosphorylation has also been shown to regulate its protein-protein interactions. Phosphorylation of this residue is thought to enhance CaMKII binding to isolated PSDs (Strack et al, 1997b), densin-180 (Strack et al, 2000), and the Nmethyl-D-aspartate receptor (NMDAR) subunits NR2B (Strack and Colbran, 1998;Bayer et al, 2001;Leonard et al, 2002), NR1 (Leonard et al, 2002), and NR2A (Gardoni et al, 1999). Furthermore, T286 phosphorylation has been reported to decrease the dissociation rate of CaMKII that has been bound to the PSD (Shen et al, 2000;Bayer et al, 2006;Yoshimura and Yamauchi, 1997;Dosemeci et al, 2002) (but see (Strack et al, 1997b)).…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that other mechanisms of kinase activation are involved in both brain areas. CaM kinase II can be persistently activated by interacting with other proteins, including the NMDA receptor and ether-a-go-go (Eag) K + channel (Strack et al, 2000;Bayer et al, 2001;Sun et al, 2004). These non-canonical mechanisms of activation of CaM kinase II could be a preferential target of antidepressants, because they also seem to be involved at synaptic level (see next section).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the kinase autophosphorylation was reduced in synaptosomes from both areas, particularly in HC where up-regulation of Ca 2 + -independent activity was maximal. This suggests that the modulation of CaM kinase II activity by antidepressants at synaptic terminals is independent from autophosphorylation and may involve protein-protein interactions (Strack et al, 2000;Bayer et al, 2001;Sun et al, 2004). Indeed, it has been shown that interaction of CaM kinase II with subunits of the NMDA receptor or the Eag potassium channel activates the kinase independent on autophosphorylation (Bayer et al, 2001;Sun et al, 2004).…”
Section: Chronic Antidepressant Treatments Induce a Redistribution Ofmentioning
confidence: 99%
See 1 more Smart Citation